Simulation, Design and Construction of a 15 Kv Dc Power Supply Using Voltage Multiplier Circuits - Karim, Anayet (2005)
This thesis describes a PSpice and PSCAD based design and implementation of high voltage DC power supply at 15 kV output. It presents the detail description of the simulation, design, development and implementation of hardware for high voltage DC power supply in the laboratory. The conventional technique is used because the designed DC power supply is intended to be applied either for impulse generator charging units or laser excitation. The main components of a DC power supply are rectifier diodes and capacitors. The output of the power supply is a fairly smooth DC voltage. The simplest unregulated power supply consists of three parts namely, the transformer unit, the rectifiers unit and the capacitors unit. The main emphasis of this project is on the simulation, and design by using two different software (mentioned earlier) to compare simulation results as well as experimental results of the high voltage DC power supply. The economic feasibility of designing doubler or tripler based high voltage DC power supply and observation of the fact that simulated and experimental values are different. A piece of high voltage generator is made available to the department. Simulation and experimental results are presented. It has been observed that the results are in agreement except due to the tolerances of the capacitor. The system hardware has been implemented and tested in the laboratory.